The Relationship between Knowledge and the Role of Parents and Completeness of Basic Immunization for 2-Year-Old Children - Zuliatin, Nur Ima; Aisyah, Harnina Samantha; Maghfuroh, Lilis; Rahman, Taufiqur (Jurnal Surya, 2024)
Introduction: Immunization is one way to prevent infectious diseases, especially diseases that can be prevented by immunization given to children, infants, adolescents and adults. The purpose of this scientific paper is to determine the knowledge and role of parents with basic immunization in children aged 2-5 years Methods: The research design used a cross-sectional design. Sampling was taken using the Random Sampling technique. The independent variables are the knowledge and role of parents, the dependent variable is the completeness of basic immunization. The instruments used were questionnaires and KIA books. Data analysis used the SPSS 22.0 test. Results: The results of this study indicate that out of 62 parents, 29 parents were found to have good knowledge so that most (74.4%) of basic immunization was complete and 17 parents played a sufficient role so that almost some (41.5%) of basic immunization was complete. Conclusion: There is a relationship between knowledge and the role of parents with the completeness of basic immunization in children aged 2-5 years Keywords: Completeness of Basic Immunization, Knowledge, Role of Parents